Organizational Capacity: Navigating Complexity in Integrated Primary Healthcare in Rural Indonesia - Mansur, Syusanty A; Badu, Badu; Nara, Nurdin; Ibrahim, Muhammad Akmal (AIBPM Publisher, 2024)
This study explores the organizational capacity of the Jeneponto District Government in implementing the Integrated Local Health System (ILP), focusing on infrastructure, technology, and financial resources. Using a qualitative case study approach, data were gathered through interviews, observations, and document analysis involving key stakeholders such as government officials, health workers, and community members. The findings highlight several challenges, including inadequate health infrastructure, limited availability of medicines, and a shortage of health workers in remote areas. The use of digital systems for monitoring remains suboptimal due to technical limitations and lack of ICT support. Financially, support for Posyandu operations and incentives for cadres are uneven, with budget commitments from local governments needing improvement. The study emphasizes the need for stronger organizational capacity through better infrastructure, improved digital health systems, and sufficient financing. Collaboration across sectors and firm political commitment are essential to ensuring the success of ILP and advancing primary health care services.